Transformasi dan Pengolahan Data Pelaporan Bank Umum Menggunakan Teknik Data Virtualisasi - Muhammad Firdaus; Shedriko Shedriko (Universitas Indraprasta PGRI Jakarta, 2022)
The development of data technology and its utilization is very fast, resulting in humans’ competition for innovation in the data that can be more easily processed in such a way as to meet user’s expectations. Data integration is an important aspect to make data and information are connected one and another. Weaknesses that often arise from the traditional-way of ETL (Extract-Transform-Load) are the complexity of connections from multiple sources, as well as the dependence on temporary data storage to allow data to flow from the source Database to the target Database. The application of data virtualization can provide the right solution to integrate data more effectively and more efficiently than the use of ETL methods in general. The purpose of this research is that Data Virtualization can provide features and renewable technology, making it easier for users to generate daily or monthly bank reports faster in accordance with the expectations and provisions in the Bank Indonesia (BI) regulations. Therefore, in the process of this research, R&D (Research and Development) is still considered the most appropriate method. The results of this research are solutions or commercial bank’s data processing systems that can issue the result information that will be daily / monthly reported by the users to Bank Indonesia.